Association between sociodemographic status and the T2DM-related risks in China: implication for reducing T2DM disease burden - Huang, Xin; He, Yinhui; Xu, Haiyan; Shen, Yuyan; Pan, Xiaowen; Wu, Junyun; Chen, Kai (Frontiers in Public Health, 2024)
Objective: Analyzing the association between sociodemographic status and the type 2 diabetes mellitus (T2DM)-related risks in China to reduce the disease burden of T2DM.We downloaded data from the Global Burden of Disease Study 2019 to estimate the disease burden of T2DM in China. Secondary analyses were performed by year, age, gender, summary exposure value (SEV) and socio-demographic index (SDI).In China, it is estimated that 3. 74 (3.44-4.10) million incidence, 90.0 (82.3-98.5) million prevalence, 168.4 (143.2-194.0) thousand deaths and 9.6 (7.6-11.9) million DALYs occurred in 2019, showing an increase of 96.8%, 156.7%, 162.8% and 145.4% compared to 1990. An inverse Ushaped curve was observed for the correlations between T2DM-related burden and SDI. A heavier burden was found in males. The top 4 risk factors were high body mass index (HBMI), dietary risks, air pollution and tobacco. HBMI, as the key risk, accounted for half of the disease burden of T2DM in China. Lower degree of SEV and higher level of attributable T2DM-raleted burden could be found in main risks, meaning the critical role of them in the development and progression of T2DM. AnRisks & global burden of T2DM 1990-2019 2 inverse U-shaped curve could be found in the association between age-standardized incidence, mortality and DALYs rate and SDI.The disease burden of T2DM was rapidly increased in China. Gender disparities, different age distribution and inconsistent socioeconomic levels all played an important role in it. The key risk was HBMI. With the improvement of socioeconomic level, the main risk factors for T2DM have changed from environmental factors to lifestyle factors. Targeted control and preventative strategy to address adjustable risk factors could put an end to soaring this burden.